Ethnicity-Based Multicultural Education Model - Muhammad Diwanul Mujahidin; Andika Supriadi; Ali Imron (Metafora: Education, Social Sciences and Humanities Journal, 2023)
Multicultural education is one of the foundations of education that must be instilled to provide insight and knowledge about diversity in community life, besides that multicultural education also contains a way to live in harmony with differences in ethnicity, ras, religion, culture, diverse social values in a society, especially in a family. The purpose of this research is to find out the values of multicultural education conducted at the family level between Javanese and English ethnic groups at Sugihwaras Village, this study uses qualitative methods and literature studies with the result of key research of interethnic multicultural education of the family are 1) communication between family members, 2) mutual respect between people, both in terms of religious, cultural, racial differences, the ethnicity, and social values of each other, 3) Mingle with society or always socialize.